GAMBARAN PENGETAHUAN MASYARAKAT TENTANG DAGUSIBU DI DUKUH POKO RT 02 RW 05 DESA DUWET WONOSARI KLATEN - Yuliana Salma Eka Ningsih; Yunita Dian Permata Sari; Vania Santika Putri (Jurnal Farmasindo, 2023)
Drugs are used to cure the disease that is being suffered by the patient. However, theres people who not know the actual use drugs tht are good and right, so that errors in the use of drugs often occur. DAGUSIBU (Get, Use, Save, Discard) is a Drug Awareness Family Movement Program created by the Indonesian Pharmacist Association in achieving public understanding and awareness of the correct use of drugs (Indonesian Pharmacist Association, 2014). The purpose of this study was to determine the level of knowledge about DAGUSIBU as a self-medication effort among the people of Dukuh Poko RT 02 RW 05 Duwet Village, Wonosari, Klaten. This type of research is a non-experimental research with a descriptive survey design of the community in Dukuh Poko RT 02 RW 05 Duwet Village, Wonosari, Klaten. The number of samples used were 86 respondents and the data collection technique used the total sampling method. The data obtained is the percentage of each answer to the questionnaire that has been filled in by the respondent. Based on the results of data processing, it was obtained that the level of public knowledge was in the good category, 57 (66%), 23 (27%) had sufficient knowledge, and 6 (7%) lacked knowledge. So it can be concluded that the average level of knowledge about DAGUSIBU medicine in the Dukuh Poko RT 02 RW 05 community has a good level of knowledge (80%).